Adhesion Strength of HFCVD Diamond Coating on WC Substrate Seeded with Diamond and Different Ratios of SiC Powders - Mas Ayu, Hassan; Engku Mohammad, Nazim; Sudin, Izman; Ourdjini, Ali; Tuty, Abu Bakar (Trans Tech Publications Inc., 2014)
The effect of seeding using different mixtures of diamond and silicon carbide (SiC) powders on the adhesion strength of hot-filament chemical vapor deposition (HFCVD) diamond coating on WC-6% Co substrates was studied. Diamond powders with the average grain size of 0.5 μm mixed with various concentrations of SiC powder of 175μm average grain size were employed. Diamond layers were deposited using a production unit of HFCVD technique. The diamond film morphology and the diamond quality were examined using field emission scanning electron microscope (FESEM), X-ray diffraction (XRD) and Raman spectrometer respectively. It was found that the diamond morphologies produced and the qualities were almost the same for all the seeding mixtures of pretreatment. With the blasting technique employed to determine the adhesion strength it was found that the highest diamond film adhesion strength was achieved from the seeding of a mixture of diamond with 5g/l SiC powder.